The Role of the Supervisory in Manifestation of Good Public Service: Can Resolving Problematic Notary Cases? - Tan, Winsherly; Amboro, Yudhi Priyo; Silviani, Ninne Zahara (JURNAL AKTA, 2025)
Public service is a way to realize a prosperous country. Notaries are officials who provide public services in the field of legal services for the community. The role of notaries is very important in providing legal certainty. The purpose of this study is to analyze notary services in the Riau Islands Province and the role of the supervisory board in supervising the performance of notaries. The method in this study is empirical juridical. In answering the problem in this study, the legal basis namely Law Number 2 of 2014 Concerning the Position of Notary and theoretical basis is used, namely the theory of legal certainty by Hans Kelsen and legal protection theory by Philipus M. Hadjon. The results of the study show that notary services still face various problems, especially in the Batam City area. However, there still needs to be synergy between regional and central supervisors in taking firm action against notaries who do not provide good public services. The role of regional supervisors in providing guidance to notaries is expected to provide preventive and repressive protection. The preventive role can be carried out through guidance and repressive can be carried out with the active role of supervisors at the central level in providing sanctions for permanent dismissal based on recommendations from the supervisory board at the regional level.